Social Science Learning Problems by Social Science Teachers in Padang City - Sri Mariya; Azwar Ananda; Siti Fatimah (International Journal of Educational Dynamics, 2022)
The purpose of this study was to look at the learning problems of Social Sciences (IPS) subject based on the aspect of teachers in Junior High School/SMP/SMP in Padang City. This type of research is qualitative research, with the techniques used in the data collection questionnaires and interviews as qualitative methods. The questionnaires and interviews were filled out by distributing the google form link to teachers in the Subject Teachers' Deliberation Group (MGMP). Based on the results of data identification and analysis, information on similar problems related to social studies learning in each school was obtained. Problems that occurred from the teacher's perspective are 1) Planning on the learning process, namely the lack of time in preparing the concept of the learning process, insufficient learning support books, and limited supporting facilities in planning on learning concept for each subtopic; 2) Implementing the learning process, namely limited student books and low student interest; and 3) The learning assessment process is that there are still many students who are failed based on the characteristics of the student assessment.